Seasonal Variation in the Susceptibility of Pomfret Lipids to Autoxidation - P.G, Viswanathan Nair; T.V., sankar (Fishery Technology, 2025)
Seasonal variations in the lipid content of silver pomfret (Pampus argenteus) and the extent of peroxide formation of these lipids were studied. Lipid content of small fish (283-400 g) was generally lower than that of big fish (650-813 g) in any season. Maximum lipid content was found during April to June and peroxide formation was maximum during this period. Peroxide formation was more in the lipids of small fish compared to the lipids of large fish. The relationship between peroxide formation and degree of unsaturation was not linear. The level of free fatty acids in the lipids did not affect the rate of formation of peroxides significantly.